Mobile Accounting Systems: Traditional vs. Modern Approaches - Alnoor Malla, Hamza Seefaldin; Rusma Anieza Ruslan; Munirah Mohd Yusof (Journal of Applied Science, Technology and Computing, 2025)
Mobile accounting systems have revolutionized modern financial management by providing flexible access to financial data and improving operational efficiency. This study examines the evolution from traditional desktop-based accounting software to contemporary mobile solutions supported by cloud computing, real-time synchronization, and strengthened security protocols. Key features of modern mobile accounting include enhanced accessibility, automated data entry, integration with enterprise applications and advanced analytics for informed decision-making. Despite these advantages, challenges persist, such as user resistance, data security concerns, integration issues and the need for adequate training. New developments in artificial intelligence, interface design and security are expected to further influence future adoption. This study provides an overview of the developments, capabilities, drivers and barriers of mobile accounting systems and highlights their growing importance in today’s financial landscape.